2017
DOI: 10.1002/jcp.26193
|View full text |Cite
|
Sign up to set email alerts
|

Regulating osteogenesis and adipogenesis in adipose‐derived stem cells by controlling underlying substrate stiffness

Abstract: Cells reside in a complex microenvironment (niche) in which the biochemical and biophysical properties of the extracellular matrix profoundly affect cell behavior. Extracellular stiffness, one important bio-mechanical characteristic of the cell niche, is important in regulating cell proliferation, migration, and lineage specification. However, the mechanism by which mechanical signals guide osteogenic and adipogenic commitment of stem cells remains difficult to dissect. To explore this question, we generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 64 publications
3
55
0
Order By: Relevance
“…Stem cells differentiate into muscle cells on soft substrates and osteoblasts on harder substrates [86,87]. Another study supported this finding, and stem cell on soft materials when stiffness is less than 0.05 kPa could promote neural differentiation effectively, while hard stiffness materials (>40 kPa) promoted osteogenic differentiation effectively [88,89], which could be related to the Wnt signal pathway [90]. However, there is no agreement on the optimal stiffness for stem cells to differentiate into neurons, muscle cells, cartilage cells, and osteoblasts [86,91].…”
Section: Stiffness Effectsmentioning
confidence: 79%
“…Stem cells differentiate into muscle cells on soft substrates and osteoblasts on harder substrates [86,87]. Another study supported this finding, and stem cell on soft materials when stiffness is less than 0.05 kPa could promote neural differentiation effectively, while hard stiffness materials (>40 kPa) promoted osteogenic differentiation effectively [88,89], which could be related to the Wnt signal pathway [90]. However, there is no agreement on the optimal stiffness for stem cells to differentiate into neurons, muscle cells, cartilage cells, and osteoblasts [86,91].…”
Section: Stiffness Effectsmentioning
confidence: 79%
“…55,56 The results of the studies reported herein demonstrate that osteogenesis may be partially due to the rough topography of LOG nanoparticles, further supported by published studies. [57][58][59][60][61][62]…”
Section: Discussionmentioning
confidence: 99%
“…Matrix stiffness, a biophysical cue in the cell microenvironment, played important roles in stem cell differentiation [ 24 26 ]. Mesenchymal stem cells (MSCs) [ 27 ], adipose-derived stem cells (ADSCs) [ 28 ], and umbilical cord mesenchymal stem cells (UCMSCs) [ 11 ], which were cultured on substrates with different stiffness, have been shown to possess diverse lineage commitments. MSCs would differentiate toward bone, muscle, or neuronal lineages as they grew on substrates with high, medium, or low stiffness, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%